Análisis del consumo de calzado femenino pre pandemia y post pandemia en la ciudad de Ambato - Pintado Alvarez, Joselyn Carolina (2023)
The research project carried out focuses on the comparative study of the consumption of casual - formal women's footwear in the city of Ambato. The objective The main thing is to relate the changes that footwear shows in the pre-pandemic period, pandemic and post-pandemic in the companies Bettini, Dacris, Armandiny and Que Cueros, which are recognized factories that have managed to keep their facilities active even after the pandemic. To carry out this study, various data collection strategies, such as interviews and observation sheets. One of the relevant findings is the importance of the materials used in the design of footwear collections in the different periods of the pandemic. In this sense, leather stands out as the main material in the manufacture of footwear feminine casual - formal. Consumers value durability, strength and aesthetics of the final product. Regarding the opinions on the companies Bettini, Dacris, Armandiny and Que Cueros, data was obtained that reflected the perception of businessmen in reference to the quality of the footwear, distribution channels, materials and supplies and raw material. These opinions helped to understand the strengths and areas for improvement of each company, providing valuable information for the development of strategies marketing and continuous improvement.